A one-year application of the Veneto air quality modelling system: regional concentrations and deposition on Venice lagoon. (8th February 2011) - Benassi, Alessandro; Dalan, Fabio; Gnocchi, Alessandro; Maffeis, Giuseppe; Malvasi, Giampiero; Liguori, Francesca; Pernigotti, Denise; Pillon, Silvia; Sansone, Maria; Susanetti, Laura
The Po valley is one of the most polluted area in Europe regarding ozone and PM10. To support policy-makers to implement programmes to reduce air pollution, the Veneto Region Environmental Protection Agency has set a state-of-the-art modelling system. Comparison between model results and measurements illustrates a fairly good agreement for NO2 annual mean concentration and deposition levels and daily maximum O3 levels. The disagreement for PM10 results suggests the need of further improvements in the emission inventory and the meteorogical pre-processing. The aim of this application is to estimate atmospheric loads on the Venice lagoon through the model's deposition computation.